Efficacy of (68Ga)Ga-FAPI-PET as a non-invasive evaluation method of liver fibrosis: short communication - Mori, Yuriko; Tamburini, Katharina; Novruzov, Emil; Schmitt, Dominik; Mavriopoulou, Eleni; Loosen, Sven H.; Roderburg, Christoph; Watabe, Tadashi; Kratochwil, Clemens; Röhrich, Manuel; Alavi, Abass; Haberkorn, Uwe; et al. (Annals of nuclear medicine, 2025)
Liver fibrosis is a chronic fibrosing hepatic disorder following recurrent injury, characterized by the excessive accumulation of extracellular matrix. Early detection has a great clinical impact because 80-90% of hepatocellular carcinomas are known to develop in fibrotic or cirrhotic (end-stage fibrotic) livers. PET imaging with FAP ligands exhibited highly promising results in recent years to visualize fibrosis in various organs due to the crucial role of activated fibroblasts in fibrosing processes. However, still little is known about the efficacy of FAP imaging in liver fibrosis. Thus, we sought to investigate the potential of FAPI-PET in a cohort of oncological and non-oncological patients.
Im Titel erscheint "69Ga" in eckigen Klammern
Im Titel erscheint 68 hochgestellt
Online verfügbar: 06. März 2025
Gesehen am 12.09.2025